2011
DOI: 10.3928/01477447-20111021-16
|View full text |Cite
|
Sign up to set email alerts
|

Lower-limb Amputations in Patients With Diabetes Mellitus

Abstract: It is estimated that approximately 23.6 million people in the United States have diabetes mellitus. With adequate control of this disease and appropriate foot care and basic surveillance, many patients can lead active and healthy lifestyles. However, some patients experience complications associated with poorly controlled glucose levels, including lower-extremity ulcerations and infections. When conservative measures have failed in treating these conditions, a lower-extremity amputation is an option for patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
0
5
0
2
Order By: Relevance
“…and circulatory complications (8), as well as with lower-limb amputation (9) and comorbid mental illness (10). It is, therefore, unsurprising that premature death occurs more frequently in this population (11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…and circulatory complications (8), as well as with lower-limb amputation (9) and comorbid mental illness (10). It is, therefore, unsurprising that premature death occurs more frequently in this population (11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Diabetic, pressure, and vascular ulcers are the major forms of chronic wounds [ 11 , 12 ]. Due to peripheral vascular disease, reduced blood flow and thus reduced tissue nutrition and oxygenation can lead to increased vulnerability of the skin to pathogens from the surrounding microbiota [ 9 , 12 ]. Poorly treated decubitus ulcers in bedridden or elderly patients can even cause sepsis, especially in nosocomial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Early planning and teaching regarding stump care is standard precautions that have been considered for preparing the patient for continuity of care before discharge (12) . It has been consistently shown that the best results of diabetic stump care occur when clinical pathway /an interdisciplinary approach is taken toward treatment (13) .…”
Section: Introductionmentioning
confidence: 99%